Low altitude drone aerial imagery for dugong sightings: A case study in Pulau Sibu, Johor - Ahmad, Zuhairi; Kassim, Zaleha; Ayob, Ahmad Faezal; Md. Rosli, Nur Suhaila (Malayan Nature Society, 2019)
Routine surveys of marine population and its estimation are important for species conservation. This study proposed the use of pre-planned targeted area of low altitude aerial drone imagery and equipped with the necessary GIS usage tools. A total of 20 flights using DJI Inspire 1 drone were carried out, covering an approximate area span of 11.26km2 in crossed and pre-planned flight were transected successfully at Northwest, Southwest of Sibu Island and South of Sibu Tengah Island. The drone was flown at 100m altitude for general survey, at 50m altitude after a target location had been identified, and at 30m altitude when the dugong sightings had been confirmed. The sightings coordinates were located using DJI Go and plotted in ArcGIS for sight mapping. During the 3 days of survey undertaken, there were 8 dugong sightings (1 individual and 3 group sightings) recorded. Based on pixel analysis, the sizes of the observed dugongs ranged from 1.5m to 2.7m. A mother and calf pair was also keenly observed during this survey. This study has successfully demonstrated that the use of drone has a great potential in survey usages for continuous sighting of sensitive marine mammals such as dugongs.